Electrical grade magnesium oxide with low moisture absorption and high thermal conductivity and preparation method thereof
By forming a silicon nitride shell for electrically grade magnesium oxide, safety hazards caused by its hygroscopicity and poor thermal conductivity are solved, and the characteristics of low hygroscopicity and high thermal conductivity are achieved, and the overall performance of the product is improved.
Patent Information
- Application Number
- CN202411865905.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-07
AI Technical Summary
Electrical-grade magnesium oxide causes hydration reaction due to hygroscopicity, which produces magnesium hydroxide, which causes the volume of the filler to expand and destroy the heating pipe, posing a major safety hazard, and its heat conduction performance is poor.
Electrical grade magnesium oxide with spherical core-shell structure, the inner core is magnesium oxide and the outer shell is silicon nitride coating, the electromelted magnesium oxide is coated through coating slurry, and multi-stage preheating is carried out under nitrogen atmosphere and nitriding treatment to form a silicon nitride shell.
It has achieved low moisture absorption and high thermal conductivity of electrical grade magnesium oxide, can withstand high temperatures, excellent moisture-proof insulation performance, improved thermal conductivity, high spherical shape, and improved fluidity and filling efficiency.
Smart Images

Figure CN119390096A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material preparation, and in particular to electrical-grade magnesium oxide with low moisture absorption and high thermal conductivity and a preparation method thereof. Background Art
[0002] Electrical grade magnesium oxide is widely used as a filler for electric heating appliances because of its high resistance, high voltage resistance, low leakage current and high thermal conductivity. However, electrical grade magnesium oxide is hygroscopic, and hygroscopic water will react with magnesium oxide to form magnesium hydroxide. The density of magnesium hydroxide is lower than that of magnesium oxide, which can easily lead to the volume expansion of the filler, thereby damaging the heating tube, causing leakage or even explosion of the heating tube, posing a major safety hazard.
[0003] In order to solve the above problems, the surface of magnesium oxide powder particles needs to be inertized. The commonly used treatment methods are: using organic silicon to modify and cover magnesium oxide powder, and further pyrolyzing on the basis of organic silicon modification to form magnesium oxide powder with silicon dioxide on the surface. Or, heat treatment of high-silicon magnesium oxide allows endogenous silicon to melt and seep out to coat the surface of magnesium oxide powder.
[0004] The silicon dioxide coated magnesium oxide formed by the above method has excellent hydrophobicity and high temperature resistance. However, since the thermal conductivity of silicon dioxide is one order of magnitude lower than that of magnesium oxide, the silicon dioxide coating cannot exert the original thermal conductivity of magnesium oxide, resulting in a decrease in the thermal conductivity of the heating tube.
[0005] Therefore, facing the great demand for high-temperature electrical-grade magnesium oxide, based on the current development status, this field still lacks an electrical-grade magnesium oxide that is resistant to high temperatures, has low moisture absorption, and has high thermal conductivity. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides an electrical-grade magnesium oxide with low moisture absorption and high thermal conductivity and a preparation method thereof, which has the characteristics of high temperature resistance, low moisture absorption, high thermal conductivity and good sphericity, and solves the problem that electrical-grade magnesium oxide powder is easily affected by moisture and has poor thermal conductivity.
[0007] To achieve the above object, the technical solution adopted by the present invention is: to provide an electrical grade magnesium oxide with low moisture absorption and high thermal conductivity, wherein the electrical grade magnesium oxide has a spherical core-shell structure, the core is magnesium oxide, the shell is a silicon nitride coating, and the thickness of the silicon nitride layer is 0.5-100nm.
[0008] The magnesium oxide in this application is high-purity fused magnesium oxide. The surface of the high-purity fused magnesium oxide is covered with a silicon nitride coating, and the particles are shaped into spheres, which not only makes the electrical grade magnesium oxide powder resistant to high temperature and moisture, but more importantly, ensures the thermal conductivity of magnesium oxide and improves the fluidity and filling efficiency of the powder.
[0009] The method for preparing low-hygroscopicity, high-thermal-conductivity electrical-grade magnesium oxide in the present application comprises the following steps:
[0010] The fused magnesia powder is obtained by crushing, screening and magnetic separation of fused magnesia blocks with a magnesium content of 95-99.9%wt;
[0011] The silicon powder and the silica sol are stirred and mixed and then filtered to obtain a coating slurry;
[0012] The fused magnesia powder is coated with a coating slurry, and then dried and sieved to obtain silicon-coated fused magnesia powder;
[0013] In a nitrogen atmosphere, the silicon-coated fused magnesia powder is subjected to multi-stage preheating treatment and nitriding treatment, so that the silicon powder on the surface of the silicon-coated fused magnesia powder is nitrided to form molten silicon nitride, and finally cooled and shaped to obtain high-temperature electrical grade magnesia powder.
[0014] Furthermore, the mass ratio of the silicon powder to the fused magnesium oxide powder is 0.1-0.3:1;
[0015] The mass ratio of the silica sol to the fused magnesium oxide powder is 0.05-0.4:1.
[0016] Furthermore, the temperature of the nitriding treatment can be selected to be 1500-2000° C., and the nitriding time can be selected to be 15-20 min.
[0017] Furthermore, the high temperature electrical grade magnesium oxide powder has a core-shell structure, the core is magnesium oxide, the shell is silicon nitride, and the thickness of the silicon nitride layer is 0.5-100 nm.
[0018] Furthermore, the mass ratio of silicon nitride to magnesium oxide in the high-temperature electrical grade magnesium oxide powder obtained after the nitridation treatment is 0.1 to 10%.
[0019] Furthermore, the high temperature electrical grade magnesium oxide powder is spherical, and the sphericity is 0.98-1.00.
[0020] Furthermore, the method of multi-stage preheating treatment is: firstly, the silicon-coated fused magnesia powder is subjected to primary preheating treatment at a temperature of 150-200°C for 15-20 minutes, and then, under the transportation effect of nitrogen, the silicon-coated fused magnesia powder after the primary preheating treatment is transported to a temperature of 400-600°C for secondary preheating treatment for 15-20 minutes.
[0021] Furthermore, the particle size of the fused magnesium oxide powder can be selected to be 50-1000 mesh; and / or
[0022] The dried fused magnesia powder is sieved to remove ultrafine powder with a particle size less than 1000 mesh to obtain silicon-coated fused magnesia powder.
[0023] Furthermore, the particle size of the silicon powder is 0.1-0.3 μm, and the purity is 99.5%-99.9%.
[0024] Furthermore, during the coating process, the inlet air temperature can be selected to be 65-70°C, and the outlet air temperature can be selected to be 40-50°C.
[0025] Furthermore, the drying temperature can be selected to be 100-120°C.
[0026] Another object of the present invention is to provide an electrical grade magnesium oxide with low moisture absorption and high thermal conductivity, characterized in that it is prepared by the above method.
[0027] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:
[0028] First, the present invention coats the fused magnesium oxide with a coating slurry, covers the surface of the high-purity fused magnesium oxide with a silicon nitride coating, forms a fully covered silicon nitride shell layer, isolates water vapor, and prevents the magnesium oxide powder from absorbing moisture. At the same time, because silicon nitride has a higher thermal conductivity than magnesium oxide, it achieves inert modification without reducing the thermal conductivity of the particles, so that the electrical grade magnesium oxide powder can withstand high temperatures and moisture resistance, and more importantly, ensures the thermal conductivity of magnesium oxide.
[0029] Second, the low-hygroscopicity and high-thermal-conductivity electrical-grade magnesium oxide obtained by the present invention has been tested. Compared with ordinary electrical-grade magnesium oxide powder, it can withstand high temperature (2000°C), has a low moisture absorption rate (≤0.3%), has excellent moisture-proof and insulating properties (>1000MΩ), and a thermal conductivity of >50W / mK. By improving the above performance indicators, the various electrical performance indicators of the terminal product electric heating element and electric heating tube are fully improved, thereby improving the overall terminal product quality.
[0030] Third, the present invention uses step preheating to make the silicon micropowder fit tightly on the magnesium oxide particles, and then undergoes high-temperature nitriding treatment in a high-temperature plasma torch flame zone in a nitrogen atmosphere to form a molten nitrided shell layer to fill the pores on the surface of the particles and form a sphere, so that the spherical high-temperature electrical grade magnesium oxide obtained has a high sphericity (≥0.98) and is easy to flow (flow rate <95s / 100g). BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0032] Figure 1 The present invention is a flow chart of the production method of electrical grade magnesium oxide powder with low moisture absorption and high thermal conductivity;
[0033] Figure 2 This is the SEM morphology picture of sample 1#. DETAILED DESCRIPTION
[0034] The following is combined with Figure 1-2 The present invention is further described in detail with reference to the accompanying drawings and examples.
[0035] Unless otherwise specified, the raw materials and catalysts in the examples of this application were purchased through commercial channels.
[0036] Example
[0037] Example 1
[0038] This embodiment discloses a method for preparing electrical grade magnesium oxide with low moisture absorption and high thermal conductivity. The preparation process is as follows: Figure 1 As shown, in order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below.
[0039] A method for preparing electrical grade magnesium oxide with low moisture absorption and high thermal conductivity comprises the following steps:
[0040] Take 10 kg of silicon powder and 10 kg of silica sol, stir and mix them evenly, then filter to obtain a coating slurry;
[0041] Taking fused magnesia blocks with a magnesium content of 95-99.9%wt, crushing, screening and magnetic separation to obtain fused magnesia powder;
[0042] 100 kg of 40-325 mesh fused magnesium oxide powder is loaded into a coating machine, the coating machine spray gun air compressor and peristaltic pump are started, the inlet temperature is set to 65° C. and the outlet temperature is set to 40° C., and the fused magnesium oxide powder is coated; the drying temperature is set to 100° C., the fused magnesium oxide powder after the coating is dried, and then the dried fused magnesium oxide powder is sieved to remove the ultrafine powder with a particle size less than 1000 mesh to obtain silicon-coated fused magnesium oxide powder;
[0043] The silicon-coated fused magnesium oxide powder was preheated to 150°C, and then entered into a high-temperature preheating furnace under the pneumatic transport of nitrogen, and was secondary preheated to 400°C in a nitrogen atmosphere; the silicon-coated fused magnesium oxide powder after secondary preheating entered into a high-temperature nitriding furnace with nitrogen for nitriding treatment, and in a nitrogen atmosphere, the silicon-coated fused magnesium oxide powder was heat treated in a 1500°C plasma torch flame zone for 15 minutes to undergo nitriding, melting and spheroidization, and finally, after cooling and shaping, spherical high-temperature electrical grade magnesium oxide was obtained, which was named sample 1#.
[0044] Example 2
[0045] Take 20 kg of silicon powder and 20 kg of silica sol, stir and mix them evenly, then filter to obtain a coating slurry;
[0046] Taking fused magnesia blocks with a magnesium content of 95-99.9%wt, crushing, screening and magnetic separation to obtain fused magnesia powder;
[0047] Take 100kg of 40-325 mesh fused magnesium powder and load it into the coating machine, start the coating machine spray gun air compressor and peristaltic pump, set the air inlet temperature to 65℃ and the air outlet temperature to 45℃, and coat the fused magnesium oxide powder. Set the drying temperature to 110℃, dry the fused magnesium oxide powder after coating, and then sieve the dried fused magnesium oxide powder to remove the ultrafine powder with a particle size less than 1000 mesh to obtain silicon-coated fused magnesium oxide powder;
[0048] The silicon-coated fused magnesium oxide powder was preheated to 170°C, and then entered the high-temperature preheating furnace under the pneumatic transport of nitrogen, and was preheated to 500°C in the nitrogen atmosphere. After the secondary preheating, the silicon-coated fused magnesium oxide powder entered the high-temperature nitriding furnace with nitrogen for nitriding treatment. In the nitrogen atmosphere, the silicon-coated fused magnesium oxide powder was heat treated in the 1700°C plasma torch flame zone for 15 minutes, and nitridation, melting and spheroidization occurred. Finally, the powder was cooled and shaped to obtain spherical high-temperature electrical grade magnesium oxide, named sample 2#.
[0049] Example 3
[0050] Take 20 kg of silicon powder and 30 kg of silica sol, stir and mix them evenly, then filter to obtain a coating slurry;
[0051] Taking fused magnesia blocks with a magnesium content of 95-99.9%wt, crushing, screening and magnetic separation to obtain fused magnesia powder;
[0052] Take 100kg of 40-325 mesh fused magnesium powder and load it into the coating machine, start the coating machine spray gun air compressor and peristaltic pump, set the air inlet temperature to 70℃ and the air outlet temperature to 50℃, and coat the fused magnesium oxide powder. Set the drying temperature to 120℃, dry the fused magnesium oxide powder after coating, and then sieve the dried fused magnesium oxide powder to remove the ultrafine powder with a particle size less than 1000 mesh to obtain silicon-coated fused magnesium oxide powder;
[0053] The silicon-coated fused magnesia powder was preheated to 200°C, and then entered the high-temperature preheating furnace under the pneumatic transport of nitrogen, and was preheated to 600°C in a nitrogen atmosphere. After the secondary preheating, the silicon-coated fused magnesia powder entered the high-temperature nitriding furnace with nitrogen for nitriding treatment. In the nitrogen atmosphere, the silicon-coated fused magnesia powder was heat treated in the 2000°C plasma torch flame zone for 20 minutes to undergo nitriding, melting and spheroidization. Finally, the powder was cooled and shaped to obtain spherical high-temperature electrical grade magnesia, named sample 3#.
[0054] Comparative Example
[0055] Comparative Example 1
[0056] The difference from Example 1 is that the silicon-coated fused magnesium oxide powder is only subjected to primary preheating and no secondary preheating. The silicon-coated fused magnesium oxide powder after the primary preheating is directly subjected to nitridation treatment, and the obtained magnesium oxide is named Sample 4#.
[0057] Comparative Example 2
[0058] The difference from Example 1 is that magnesium oxide is coated with a silicon dioxide coating, and the sample is named Sample 5#.
[0059] Performance Testing
[0060] The performance of the spherical high temperature electrical grade magnesium oxide prepared in Example 1-3, the ordinary high temperature electrical grade magnesium oxide powder in the control example, and the magnesium oxide prepared in Comparative Example 1-2 are compared in Table 1-2. The control example is ordinary high temperature electrical grade magnesium oxide powder produced by Liaoning Rongbang Technology Co., Ltd. with a magnesium content of 95%wt.
[0061] Performance Test 1
[0062] The SEM morphology analysis was performed on samples 1# to 3# respectively. Table 1 shows the silicon nitride coating thickness of samples 1# to 3#.
[0063] Table 1 Silicon nitride coating thickness of different samples
[0064]
[0065] Take sample 1# as a typical example. Figure 2 This is the SEM morphology picture of sample 1#. Figure 2 It can be seen that the outside of the MgO particles is covered by a silicon nitride coating.
[0066] Performance Test 2
[0067] After samples 1#~3#, comparative examples 1-2 and ordinary high-temperature electrical grade magnesium oxide powder were made into standard electric heating elements (Note: sample tube SUS304 steel tube length: 500mm 110V / 500W), the water absorption, thermal conductivity and flow rate were determined according to GB / T8508-1996; the insulation resistance was determined according to GB / T 13033.1-2007; the sphericity was determined according to GB / T 37406-2019, and the test results are shown in Table 2.
[0068] Table 2
[0069]
[0070] As can be seen from Table 2, since Comparative Example 1 did not undergo secondary preheating treatment, a large temperature gradient was formed on the particle surface during high-temperature nitridation, resulting in uneven nitridation layer coating, affecting water absorption and thermal conductivity; Comparative Example 2 used a silicon dioxide coating to coat magnesium oxide, and since the thermal conductivity of silicon dioxide was worse than that of magnesium oxide, the thermal conductivity of the product decreased. The high-temperature electrical grade magnesium oxide powder prepared by the present invention has greatly improved insulation performance, thermal conductivity, and sphericity, and greatly reduced water absorption and flow rate.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing electrical grade magnesium oxide with low moisture absorption and high thermal conductivity, characterized in that: The steps include: The fused magnesia powder is obtained by crushing, screening and magnetic separation of fused magnesia blocks with a magnesium content of 95-99.9%wt; The silicon powder and the silica sol are stirred and mixed and then filtered to obtain a coating slurry; The fused magnesium oxide powder is coated with a coating slurry, and then dried and sieved to obtain silicon-coated fused magnesium oxide powder; In a nitrogen atmosphere, the silicon-coated fused magnesia powder is subjected to multi-stage preheating treatment and nitriding treatment, so that the silicon powder on the surface of the silicon-coated fused magnesia powder is nitrided to form molten silicon nitride, and finally cooled and shaped to obtain high-temperature electrical grade magnesia powder.
2. The preparation method according to claim 1, characterized in that: The mass ratio of silicon powder to fused magnesium oxide powder is 0.1-0.3:1; The mass ratio of the silica sol to the fused magnesium oxide powder is 0.05-0.4:
1.
3. The preparation method according to claim 1, characterized in that: The temperature of the nitriding treatment can be selected as 1500-2000° C., and the nitriding time can be selected as 15-20 minutes.
4. The preparation method according to claim 1, characterized in that: The high temperature electrical grade magnesium oxide powder has a core-shell structure, the core is magnesium oxide, the shell is silicon nitride, and the thickness of the silicon nitride layer is 0.5-100nm.
5. The preparation method according to claim 4, characterized in that: The mass ratio of silicon nitride to magnesium oxide in the high-temperature electrical grade magnesium oxide powder is 0.1-10%.
6. The preparation method according to claim 1, characterized in that: The high temperature electrical grade magnesium oxide powder is spherical, and the sphericity is 0.98-1.
00.
7. The preparation method according to claim 1, characterized in that: The multi-stage preheating method is: the silicon-coated fused magnesium oxide powder is first preheated at 150-200°C for 15-20 minutes, and then transported to 400-600°C for secondary preheating under the action of nitrogen, and preheated for 15-20 minutes.
8. The preparation method according to claim 1, characterized in that: The particle size of the fused magnesium oxide powder can be selected to be 50-1000 meshes.
9. The preparation method according to claim 1, characterized in that: The particle size of the silicon powder is 0.1-0.3 μm, and the purity is 99.5%-99.9%.
10. A low hygroscopicity, high thermal conductivity electrical grade magnesium oxide, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Cited By
Silicon nitride / magnesium silicon nitride powder with core-shell structure as well as preparation method and application of silicon nitride / magnesium silicon nitride powder
CN121553909A
Preparation method of moisture-resistant spherical magnesium oxide
CN121778759A